in vitro Antibacterial Activities of Antibiotics and Traditional Chinese Medicinal Herb Extracts on Escherichia coli and Staphylococcus aureus - Sun, Hong-Yan; Li, Zeng-Bo; Liu, Wen-Xing; Wang, Xiao-Yun; Zhang, Tian-Jing; Feng, Zhi-Jun (Asian Journal of Chemistry, 2013)
The present study has been aimed to assess the antibacterial effects of the gentamycin sulfate by agar-well diffusion method against Escherichia coli and penicillin against Staphylococcus aureus. Aspects on the antibacterial mode of action of Chinese medicinal herb extracts have also been characterized. The minimum inhibitory concentration (MIC) of gentamycin sulfate was 8 μg mL-1 and those of penicillin was 0.5 μg mL-1, with the diameter of inhibition zone was 8.5 and 7.5 mm, respectively. And the rational pH value of the working antibiotics was 5, the reasonable preservation temperature should below 80 and 60 °C for gentamycin sulfate and penicillin, respectively. Meanwhile, both ethanolic extracts of Forsythia suspensa (forsythia) and Taraxacum ohwianum (taraxacum) had a better antibacterial effect to S. aureus, however E. coli only sensitive to Forsythia suspensa (forsythia). Thus, antibiotics combined with Chinese herb Forsythia suspensa (forsythia) may have better antibacterial effect to bacterium.